P05.75 Surgery followed by fractionated radiosurgery on the tumor bed in patients with single large brain metastases from solid tumor: preliminary results of a phase II study. (19th September 2018) - Navarria, P; Clerici, E; Pessina, F; Franzese, C; Bello, L; Riva, M; Toschi, L; Masci, G; Comito, T; Scorsetti, M
Abstract: Background: Brain metastases (BMs) occur in 20%-40% of adult cancer patients, and their incidence has increased from 2 to 5 times over the past 40 years. Treatment options include surgery, whole-brain radiation therapy (WBRT), and stereotactic radiosurgery (SRS). As a single modality, none of these are able to obtain an adequate local control (LC) of large BMs (≥2.1 cm), and therefore a combined approach, is recommended. We designed a prospective phase II study aimed to assess the benefit of surgical resection followed by fractionated radiosurgery (FSRS) on the tumor bed, instead of postoperative WBRT, for patient with single large brain metastases from solid tumor. The potential advantage of this treatment is to improve local control and to reduce toxicity compared with WBRT after surgical resection. Primary endpoint was local control rate; secondary endpoints incidence of new brain metastases, and patients overall survival. Material and Methods: Patients with age >18 years, KPS ≥70, oligometastatic disease, controlled primary tumor and extracranial metastases, single BM ≥ 2.1 cm, and estimated survival ≥3 months were enrolled. Patients underwent previous WBRT were excluded. Surgical resection was performed with the aim to maximally (>95%) remove the tumor. Within 1 month from surgery, a fractionated SRS was performed on the tumor bed for a total dose of 30 Gy in 3 daily fractions. Outcome was evaluated by neurological examination and MRI performed 2 months after treatment and every 3 months thereafter. Response in site of treatments was assessed according to RANO criteria. Results: Between 2014 and May 2018, 122 patients were enrolled, 56 female and 66 male with a median age of 49 years. The most common primary tumor was Non-Small Cell Lung Cancer (47%), followed by breast cancer (27%) and melanoma (10%). The median follow-up was 22 months (range 7–48 months). The 1, 2-year LC rate were 98%, and 98%. Forty-two (34%) patients had new BDP at a median time of 19 months. The median 1, 2-year overall survival were 24 months, 91.3% and 73%. At the last observation time, 27 patients (22%) were dead and 95 patients (78 %) were alive. No detrimental effect on neurocognitive functions was recorded. Conclusion: Fractionated SRS after surgical resection is a safe and feasible option in patients with large brain metastases and oligometastatic disease.